1991
DOI: 10.1007/bf00197565
|View full text |Cite
|
Sign up to set email alerts
|

“Sink” regulation of photosynthetic metabolism in transgenic tobacco plants expressing yeast invertase in their cell wall involves a decrease of the Calvin-cycle enzymes and an increase of glycolytic enzymes

Abstract: Leaves on transgenic tobacco plants expressing yeast-derived invertase in the apoplast develop clearly demarcated green and bleached sectors when they mature. The green areas contain low levels of soluble sugars and starch which are turned over on a daily basis, and have high rates of photosynthesis and low rates of respiration. The pale areas accumulate carbohydrate, photosynthesis is inhibited, and respiration increases. This provides a model system to investigate the "sink" regulation of photosynthetic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
3
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(146 citation statements)
references
References 47 publications
9
127
3
7
Order By: Relevance
“…This disaccharide is described as a compatible solute with no net charge, and it is proposed that it can be accumulated without interfering in cellular homeostasis (Brown, 1976;Mackay et al, 1984;Mikkat et al, 1997;Miao et al, 2003;Hagemann, 2011). However, our data suggest that Suc might have an effect on cellular homeostasis, and in particular photosynthesis, possibly by sugar feedback inhibition of photosynthesis (Stitt et al, 1991). Indeed, in contrast to ML, cells grown under HL could maintain a high level of photosynthesis while exporting larger amounts of Suc in the medium and accumulating much lower amounts of Suc within their cells.…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lmentioning
confidence: 59%
“…This disaccharide is described as a compatible solute with no net charge, and it is proposed that it can be accumulated without interfering in cellular homeostasis (Brown, 1976;Mackay et al, 1984;Mikkat et al, 1997;Miao et al, 2003;Hagemann, 2011). However, our data suggest that Suc might have an effect on cellular homeostasis, and in particular photosynthesis, possibly by sugar feedback inhibition of photosynthesis (Stitt et al, 1991). Indeed, in contrast to ML, cells grown under HL could maintain a high level of photosynthesis while exporting larger amounts of Suc in the medium and accumulating much lower amounts of Suc within their cells.…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lmentioning
confidence: 59%
“…An alternative possibility for hexose sensing in the absence of any detectable cytosolic hexoses at any time during the day could involve futile cycling of Suc between the cytosol and vacuole and/or between the cytosol and apoplast (Foyer, 1987;Huber, 1989;Stitt et al, 1990). Exposure to elevated CO 2 may result in increased carbon flux to Suc.…”
Section: Discussionmentioning
confidence: 99%
“…photosynthesis may be inhibited earlier in the WT because it has higher carbohydrate levels. Consistent with this possibility is the well-established finding that source leaves adjust their photosynthetic rates in response to the demand for photoassimilates in the rest of the plant, inhibiting photosynthesis when the demand is low and increasing photosynthesis when the demand is high (sink regulation of photosynthesis) (reviewed by Turgeon, 1989;von Schaewen et al, 1990;Stitt et al, 1990;Stitt, 1991;Sonnewald and Willmitzer, 1992). It has also been observed that the rate of leaf senescence is affected by the sinksource status of the plant (Christensen et al, 1981;Bin Lazan et al, 1983;Wittenbach, 1983;Shibles et al, 1987;Guitman et al, 1991) and that photosynthetic gene expression can be modulated by carbohydrates at the transcriptional level (Sheen, 1990;Krapp et al, 1993).…”
mentioning
confidence: 83%